PENINGKATAN KEMAMPUAN GURU MENGEMBANGAKAN RPP DENGAN MENERAPKAN METODE DEMONSTRASI MELALUI SUPERVISI KUNJUNGAN KELAS - Suparti Suparti (JURNAL PENA EDUKASI, 2019)
Abstract: The purpose of this study was to improve the ability of teachers to develop a lesson plan for SD Negeri 013887 Asahan Mati Kec. Tanjung Balai. The results showed that improving the ability of teachers to develop lesson plans by applying the Demonstration method through academic supervision at SD Negeri 013887 Asahan Mati kec. Tanjung Balai can increase, namely 88% the level of the teacher's ability to develop a good lesson plan. This can be seen from the average results of previous observations supervised by the quality level of the teacher's ability to develop a learning implementation plan is 21.96 or with the quality level of the teacher's ability to develop a learning implementation plan is sufficient, the average result after being supervised is 1 the level of the teacher's ability to develop a learning implementation plan is 24, 56 or good quality level. The results of the average score of supervision II, the teacher's ability to develop a teacher learning implementation plan, was 27.04 or the quality level of the teacher's ability to develop a good learning implementation plan. The result of the data score II was 2.60 higher than the data score I. The result of the data score III was 2.48 higher than the data score II. The result of the data score III is 5.08 higher than the score I.Keywords: class visits; demonstration; supervisionAbstrak: Tujuan penelitian ini adalah untuk meningkatkan kemampuan guru mengembangkan rencana pelaksanaan pembelajaran SD Negeri 013887 Asahan Mati Kec. Tanjung Balai. Dari hasil penelitian menunjukkan bahwa meningkatkan kemampuan guru mengembangkan rencana pelaksanaan pembelajaran dengan menerapkan metode Demonstrasi melalui supervisi akademik di SD Negeri 013887 Asahan Mati kec. Tanjung Balai dapat meningkat, yaitu 88% tingkat kemampuan guru mengembangkan rencana pelaksanaan pembelajaran baik. Ini dapat diketahui dari hasil rata rata pengamatan sebelumnya disupervisi tingkat kualitas kemampuan guru mengembangkan rencana pelaksanaan pembelajaran adalah 21,96 atau dengan tingkat kualitas kemampuan guru mengembangkan rencana pelaksanaan pembelajaran cukup, hasil rata rata setelah disupervisi 1 tingkat kemampuan guru mengembangkan rencana pelaksanaan pembelajaran sebesar 24,56 atau tingkat kualitas baik. Hasil skor rata rata supervisi II tingkat kemampuan guru mengembangkan rencana pelaksanaan pembelajaran guru sebesar 27,04 atau tingkat kualitas kemampuan guru mengembangkan rencana pelaksanaan pembelajaran baik. Hasil skor data II lebih tinggi 2,60 daripada skor data I. Hasil skor data III lebih tinggi 2,48 dari pada skor data II. Hasil skor data III lebih tinggi 5,08 dari skor I.Kata kunci: demonstrasi; kunjungan kelas; supervisi